Case Report: Potential benefits of a single functional neurology intervention in athletic rehabilitation and recovery: a case study - Rey-Mota, Jorge; Escribano-Colmena, Guillermo; Navarro Jiménez, Eduardo; Laborde-Cárdenas, Carmen Cecilia; Yáñez-Sepúlveda, Rodrigo; Clemente-Suárez, Vicente Javier (Frontiers in Sports and Active Living, 2025)
This study analyze the effect of a single functional neurology session on sports performance, pain perception, fatigue perception and thermographic muscular response in an international female weightlifting athlete with incapacity to tolerate weight. Functional neurology is a discipline leveraging neuroplasticity for non-invasive recovery and performance optimization. We found how a single session of functional neurology improved load tolerance, enabling her to lift weights at pre-injury levels after just a single session of functional neurology and reduced pain perception from 80 to 0 and fatigue perception from 90 to 20 on a 100-point scale while thermographic data showed up to a 15% decrease in body temperature indicating reduced inflammation and improved muscle recovery. Then, we found how a single functional neurology intervention produced an improve in sports performance, pain and fatigue perceptions, and peripheral vascular response in an inter-national female weightlifting athlete with an initial incapacity to tolerate weight. This supports the incorporation of functional neurology into sports rehabilitation, under-scoring its potential in optimizing athletes' health and performance.